2017
DOI: 10.1007/s00213-017-4766-7
|View full text |Cite
|
Sign up to set email alerts
|

Phytocannabinoids modulate emotional memory processing through interactions with the ventral hippocampus and mesolimbic dopamine system: implications for neuropsychiatric pathology

Abstract: Growing clinical and preclinical evidence suggests a potential role for the phytocannabinoid cannabidiol (CBD) as a pharmacotherapy for various neuropsychiatric disorders. In contrast, delta-9-tetrahydrocannabinol (THC), the primary psychoactive component in cannabis, is associated with acute and neurodevelopmental propsychotic side effects through its interaction with central cannabinoid type 1 receptors (CB1Rs). CB1R stimulation in the ventral hippocampus (VHipp) potentiates affective memory formation throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 177 publications
1
15
0
Order By: Relevance
“…Out of all animal models of SCZ where CBF was studied, the THC model seems to be the least affected, as judged by the functional perfusion and structural changes. This model is based on the hypothesis that perinatal exposure to THC could induce psychiatric disorders later in life 46 , also by modulating several neurotransmitters system (DAergic, Glutamatergic and/or GABAergic) via central cannabinoid type 1 receptor 47 . Despite the positive behavioral outcome, our CBF data indicate that the THC model is hemodynamically stable, which is an unexpected result based on findings from other animal models 18,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Out of all animal models of SCZ where CBF was studied, the THC model seems to be the least affected, as judged by the functional perfusion and structural changes. This model is based on the hypothesis that perinatal exposure to THC could induce psychiatric disorders later in life 46 , also by modulating several neurotransmitters system (DAergic, Glutamatergic and/or GABAergic) via central cannabinoid type 1 receptor 47 . Despite the positive behavioral outcome, our CBF data indicate that the THC model is hemodynamically stable, which is an unexpected result based on findings from other animal models 18,44 .…”
Section: Discussionmentioning
confidence: 99%
“…CBD has antipsychotic effects [126] and may reduce the affective and cognitive deficits associated with schizophrenia, mainly through the facilitation of endocannabinoid signalling and CB1 receptor antagonism [120], the reduction of glial reactivity [127] and the normalisation of molecular and neuronal changes that take place in the mesolimbic system [70]. Hudson et al [128] also hypothesised that CBD could prevent the acquisition of emotionally irrelevant memories and reverse schizophrenia-related pathology, since the stimulation of CB1 receptors in the ventral hippocampus potentiates the formation of affective memories. To test the antipsychotic efficacy of CBD, studies with rodents and non-human primates have used the pre-pulse inhibition (PPI) of acoustic startle reflex, a paradigm that models sensorimotor gating deficits observed in several neuropsychiatric disorders [129].…”
Section: Possible Mechanisms Involved In the Protective Effects Ofmentioning
confidence: 99%
“…In addition to antipsychotic ( Leweke et al, 2012 ; McGuire et al, 2018 ; Zuardi et al, 2012 ) and anxiolytic properties ( Bergamaschi et al, 2011 ; Blessing et al, 2015 ; Crippa et al, 2011 ; Soares and Campos, 2017 ), there is some evidence to suggest that CBD may improve memory impairment across multiple domains, including working and episodic memory, as demonstrated in several preclinical models ( Avraham et al, 2011 ; Barichello et al, 2012 ; Campos et al, 2015 ; Cassol et al, 2010 ; Cheng et al, 2014a , 2014b ; Fagherazzi et al, 2012 ; Magen et al, 2009 , 2010 ; Martin-Moreno et al, 2011 ; Pazos et al, 2012 ; Schiavon et al, 2014 ; Wright et al, 2013 ), cannabis users ( Morgan et al, 2010 , 2012 ), and in cognitive impairment caused by the other main constituent of cannabis, ∆ 9 -tetrahydrocannabinol (THC) ( Englund et al, 2013 ; Hindocha et al, 2015 ), although this has not been found in all studies ( Boggs et al, 2018 ; Hindocha et al, 2018a ; Morgan et al, 2018 ). Additionally, CBD modulates emotional memory processing ( Bitencourt and Takahashi, 2018 ; Das et al, 2013 ; de Carvalho and Takahashi, 2017 ; Hindocha et al, 2015 ; Hudson et al, 2018 ; Lee et al, 2017 ; Stern et al, 2017 ; Uhernik et al, 2018 ), which may help to explain its putative therapeutic effects in post-traumatic stress disorder (PTSD; Hindocha et al, 2019 ; Shannon and Opila-Lehman, 2016 ) and anxiety disorders. However, the precise mechanisms underlying the effects of CBD on memory are unclear.…”
Section: Introductionmentioning
confidence: 99%